HOSPITAL CLASSROOM: A WAY TOWARDS INCLUSIVE EDUCATION - Caballero Soto, Solange Ana María (2014)
The Hospital Classroom should be considered in our country as a way to approach Inclusive Education; because we would be taking the challenge to integrate these students into society in a satisfactory way, considering their reality as hospitalized children/teenagers. By doing this we could achieve a process of hospitalization as favourable as possible, which means, that the patients would not only receive medical treatment but they will also be able to continue their education, and have recreation as well. Up to this moment the importance of forming teachers in this field was not fully understood, as well as their capability of alternating between “formal classroom” and “hospital classroom”. Thus, the objective of this article is to help us to meditate and understand the necessity of creating bonds between these two atmospheres.